CARICOM's inertia : who's to blame; address by Dr. the Hon. Ralph E. Gonsalves Prime Minister of St. Vincent and the Grenadines and Chairman of CARICOM - Gonsalves, Ralph E. (2014)
Explains that the disillusionment of many of the Community's critics stems from their illusions about CARICOM's nature and its institutional arrangments. Notes that it is a community of sovereign states whose centre has been deliberately designed as a weak superstructure which constantly gropes for consensus. Adds also that the Secretariat is the central administrative instrument but it possesses no authority to compel enforcement of decisions by any of the Organs and bodies which rests solely with the governments of the individual nation-states.